The South Atlantic Subtropical Anticyclone: Present and Future Climate - Reboita, Michelle Simões; Ambrizzi, Tércio; Silva, Bruna Andrelina; Pinheiro, Raniele Fátima; da Rocha, Rosmeri Porfírio (Frontiers in Earth Science, 2019)
The South Atlantic Subtropical Anticyclone (SASA) is the main feature of the atmospheric circulation over the South Atlantic Ocean, and its study is of great importance to explain many characteristics of the Brazilian weather and climate. Therefore, this study aims to present (1) a review of the literature on SASA including the drivers of the semi-permanent anticyclones and (2) the main features of the SASA in the future climate obtained through the projections of three global climate models (HadGEM2-ES, GFDL-ESM2M and MPI-ESM-MR), from the Coupled Model Intercomparison Project (CMIP5), using the Representative Concentration Pathway 8.5 (RCP8.5) scenario. SASA is zonally wider in winter and retracted to the east in summer, when it presents a more circular format. These features of the SASA in the present climate (1979-2005) are well represented by the three global climate models, which also project this same SASA seasonal pattern for the future climate (2065-2095). Considering the projections, they indicate a slightly poleward expansion of the SASA, which is associated with the widening of the Hadley cell. At the SASA core, the pressure can be similar or slightly more intense than the present climate.